Sorption-Luminescence method for determination of dipicolinic acid - Volodymyr Vasylechko; Liubomyr Shevchuk; Galyna Gryshchouk; Svitlana Bagday; Anatoliy Voloshinovskii; Olexandr Gromyko; Yaroslav Kalychak (IEEE NAP-2025, Bratislava, Slovakia, 2025)
Dipicolinic Acid (DPA) [2,6-Pyridinedicarboxylic acid] is used as a reliable biomarker for detecting and quantifying pathogenic bacterial spores contamination in both biological and aquatic environments. The possibility for DPA LM determination using the Transcarpathian clinoptilolite (CL) as an efficient Tb(III) sorbent was studied. The samples of CL-Tb(III) with a constant Ln content are obtained via Ln ions sorption from aqueous solutions at pH 5.0 on the CL in a solid phase extraction mode. The CL-Tb(III) samples were precalcined at 200 °C and treated with the ethanol or alkaline water solution, containing DPA. Obtained samples of the CL-Tb(III)-DPA luminophore were dried at 50 °C. For the excitation of the LM samples, rays with λ = 280 nm were used. The LM intensity at 544 nm was chosen as the analytical parameter for the DPA quantitative determination. The proposed sorption-luminescent method allows the determination of DPA microgram amounts and does not require toxic substances.
Метод сорбційно-люмінесцентного визначення диколінової кислоти
2025 IEEE 15th International Conference Nanomaterials: Applications & Properties (NAP)
Keywords: clinoptilolite; terbium; preconcentration; sorption-luminescence determination; dipicolinic acid